Citra Bagong sebagai Suara Wong Cilik pada Kanal YouTube Dalang Seno - Paulus Heru Wibowo Kurniawan (Rekam : Jurnal Fotografi, Televisi, Animasi, 2022)
Along with the emergence of new media, wayang kulit play have also undergone changes and adjustments to the format. Through media such as YouTube, wayang kulit shows are no longer shown as 8-9 hour long shows. This media change does not cause a paradigmatic change to the role of Punakawan, but also provides a fresher interpretation space for Punakawan (clowns) as today’s social communicators. This paper aims to examine how Bagong, one of character of Punakawan, underwent a transformation in the wayang kulit play that was broadcasted on the Dalang Seno YouTube channel, which was initiated by Ki Seno Nugroho. In this channel, Bagong is no longer shown as a side character, but as the main character in the wayang kulit narrative. In addition, this paper wants to explore the extent to which Bagong seeks as a social communicator in the context of postcolonial society as shown on the Dalang Seno channel in the midst of a pandemic.